HARMONIZATION OF NATIONAL LEGAL RIGHTS WITHIN THE FRAMEWORK OF SHARIA AN CUSTOMARY LAW IN INDONESIA - Azizah, Laila; Hafidzi, Anwar (International Journal of Multidisciplinary Reseach, 2025)
Indonesian law is the result of interaction among three major legal systems, namely customary law, Islamic law, and positive law. Within this context of legal pluralism, there is an ongoing need to harmonize Islamic normative values with the national legal system in order to develop a legal order that is both religious in character and responsive to modern demands. This study aims to analyze the conceptual and practical relationship between sharī‘ah, fiqh, and positive law within the framework of legal pluralism, as well as to assess the extent to which Islamic values can be substantively integrated into the Indonesian national legal system. This research employs a normative legal method using conceptual, comparative, and Islamic law approaches. The study relies on secondary data sources, including scholarly literature, statutory regulations, and relevant legal documents. The findings indicate that the integration of Islamic normative values into national law has been realized through several legislative instruments, such as the Law on Hajj and Umrah Administration, the Marriage Law, the Zakat Law, and the Halal Product Assurance Law. These legal frameworks reflect a dynamic synergy between the principles of maqāṣid al-sharī‘ah and the doctrine of ius constitutum in shaping laws that promote justice and public welfare (maṣlaḥah). However, this harmonization process continues to face significant challenges, particularly in the form of inconsistencies in legal politics and the tendency toward the formalization of sharī‘ah norms. This study argues that a substantive approach—through the internalization of Islamic ethical values within legal policies—is more ideal than a formalistic approach. Such an approach is essential to realizing a national legal system that is pluralistic, humanistic, and aligned with the universal spirit of raḥmatan lil ‘ālamīn.